Penentuan Lokasi PLTU Ditinjau dari Aspek Fisik dan Geografis Pada PLTU PT Bosowa Energi: Determining PLTU Location from Physical and Geographical Aspects at PT Bosowa Energi PLTU - Andi Ashari Cahyadi; Sri Widodo; Arif Nurwaskito; Habibie Anwar (Journal of Engineering Science and Technology Applications, 2023)
Choosing the correct and strategic location can make a big profit for the factory. Conversely, the factory can retain if the factory's site selection is strategic. The purpose of this study is To determine the factors in determining the location of the construction of PLTU PT. Bosowa Energy and know the climate parameter of PLTU PT. Bosowa Energy. The stages and methods of research conducted consisted of four steps: the process of research stages, methods of data retrieval, data processing and locations of data analysis, and the set of report generation. The data taken are primary and secondary; after the data is collected, data are analyzed to determine the factors determining PLTU PT location. Bosowa Energy. PLTU PT. Bosowa Energy in Bangkala Subdistrict Kabupate Jeneponto South Sulawesi Province This location has a climate among other air temperature areas ranging between 18,20 - 27,00 ̊C, rainfall area is quite wet, speed and direction of angina average ranged from 2 until 3 knots, Relative air humidity average 64.8 - 83.5%. The conclusions of this journal are the factors in determining the location of the balance of network, industrial areas, and water areas and climate parameters of rainfall, temperature, humidity, and wind speed.